tex/theory1_ex8.tex
author Eugen Sawin <sawine@me73.com>
Wed, 13 Jul 2011 14:58:35 +0200
changeset 12 847768226d25
parent 11 df83621781e1
permissions -rw-r--r--
Exercise 8.
     1 \documentclass[a4paper, 10pt, pagesize, smallheadings]{article}  
     2 \usepackage{graphicx}
     3 %\usepackage[latin1]{inputenc}
     4 \usepackage{amsmath, amsthm, amssymb}
     5 \usepackage{typearea}
     6 \usepackage{algorithm}
     7 \usepackage{algorithmic}
     8 \usepackage{fullpage}
     9 \usepackage{mathtools}
    10 \usepackage[all]{xy}
    11 \title{Theory I, Sheet 8 Solution}
    12 \author{Eugen Sawin}
    13 \renewcommand{\familydefault}{\sfdefault}
    14 \newcommand{\Pos}{\mathcal{P}os}
    15 \include{pythonlisting}
    16 
    17 \pagestyle{empty}
    18 \begin{document}
    19 \maketitle
    20 
    21 \section*{Exercise 8.1}
    22 Let $s, t \in T(\Sigma, X)$ be terms over $X$ and $p, q$ be strings over the natural numbers. We provide proofs by induction.
    23 \subsection*{1. $pq \in \Pos(s) \implies p \in \Pos(s)$ }
    24 $(IH): pq \in \Pos(t_i) \implies p \in \Pos(t_i)$ for all $0 < i \leq n$\\\\
    25 \emph{Base case:}\\
    26 From $s \in X$ or $s \in \Sigma^{(0)}$ follows $\Pos(s) = \{\epsilon\}$.\\
    27 Trivially it follows that $pq \in \Pos(s) \iff pq = \epsilon$ and $pq \in \Pos(s) \implies p \in \Pos(s)$ with $pq \notin \Pos(s)$ or $pq = p = \epsilon$. \\ 
    28 
    29 \noindent \emph{Inductive case:}\\
    30 Let $s = f(t_1, ...,t_n) \in T(\Sigma, X)$ it follows $\Pos(s) = \{\epsilon\} \cup \bigcup_{i = 1}^{n}\{ip \mid p \in \Pos(t_i)\}$.\\
    31 \begin{align*}
    32 pq \in \Pos(s) &\implies p \in \Pos(s)\\ 
    33 \iff pqr \in \Pos(f(t_1,...,t_n)) &\implies pr \in \Pos(f(t_1,...,t_n))\\
    34 \iff pqr \in \{\epsilon\} \cup \bigcup_{i = 1}^{n}\{im \mid m \in \Pos(t_i)\} &\implies pq \in \{\epsilon\} \cup \bigcup_{i = 1}^{n}\{im \mid m \in \Pos(t_i)\}\\
    35 \end{align*}
    36 By (IH) we know that $qr \in \Pos(t_i) \implies r \in \Pos(t_i)$ for all $i \leq n$ and by the left concatenation of $p$ for $0 < p \leq n$ it holds that $pqr \in \Pos(f(t_1,...,t_n)) \implies pq \in \Pos(f(t_1,...,t_n))$. \\ \qed
    37 
    38 \subsection*{2. $pq \in \Pos(s) \implies s|_{pq} = (s|_p)|_q$ }
    39 $(IH): pq \in \Pos(t_i) \implies t_i|_{pq} = (t_i|_p)|_q$ for all $0 < i \leq n$\\\\
    40 \emph{Base case:}\\
    41 From $s \in X$ or $s \in \Sigma^{(0)}$ follows $\Pos(s) = \{\epsilon\}$.\\
    42 Trivially it follows that $pq \in \Pos(s) \iff pq = q = \epsilon$ and $pq \in \Pos(s) \implies s|_{pq} = (s|_p)|_q$ with $pq \notin \Pos(s)$ or $pq = p = \epsilon$ with $s_{pq} = s = s|_p = (s|_p)|_q$.\\
    43 
    44 \noindent \emph{Inductive case:}\\
    45 Let $s = f(t_1, ...,t_n) \in T(\Sigma, X)$ it follows $\Pos(s) = \{\epsilon\} \cup \bigcup_{i = 1}^{n}\{ip \mid p \in \Pos(t_i)\}$.\\
    46 By definition we know $f(t_1, ...,t_n)|_{pqr} = t_p|_{qr}$ and from $(IH)$ it follows that $t_p|_{qr} = (t_p|_q)|_r$. \\ \qed
    47 
    48 \subsection*{3. $p \in \Pos(s) \land q \in \Pos(t) \implies (s[t]_p)|_{pq} = t|_q$ }
    49 $(IH): p \in \Pos(t_i) \land q \in \Pos(k_j) \implies (t_i[k_j]_p)|_{pq} = k_j|_q$ for all $0 < i \leq n, 0 < j \leq m$\\\\
    50 \emph{Base case:}\\
    51 From $s,t \in X$ or $s,t \in \Sigma^{(0)}$ follows $\Pos(s) = \Pos(t) = \{\epsilon\}$.\\
    52 Trivially it follows that $p \in \Pos(s) \land q \in \Pos(t) \iff p = q = \epsilon$ and $p \in \Pos(s) \land q \in \Pos(t) \implies (s[t]_p)|_{pq} = t|_q$ with $p \notin \Pos(s) \lor q \notin \Pos(t)$ or $p = q = \epsilon$ with $s[t]_p = (s[t]_p)|_{pq} = t|_q = \epsilon$.\\
    53 
    54 \noindent \emph{Inductive case:}\\
    55 Let $s = f(t_1, ...,t_n), t = g(k_1, ...,k_m) \in T(\Sigma, X)$.\\
    56 By definition we know that $f(t_1, ...,t_n)[g(k_1, ...,k_m)]_{p} = f(t_1, ...t_p[g(k_1, ...,k_m)]_\epsilon, ..t_n) = f(t_1, ...g(k_1, ...,k_m), ..t_n)$ and from $(IH)$ follows that $f(t_1, ...g(k_1, ...,k_m), ..t_n)|_{pq} = g(k_1, ...,k_m)|_q = k_q = t|_q$. \\ \qed
    57 
    58 \section*{Exercise 8.2}
    59 We use symbols $\top, \bot$ for $T, F$ respectively.
    60 
    61 \subsection*{1. $t = \neg (x \land (\top \lor y)), \sigma = \{x \mapsto \bot, y \mapsto \top \land x\}, \tau = \{z \mapsto \top, x \mapsto \top\}$}
    62 \begin{align*}
    63 \sigma(t) &= \neg (\bot \land (\top \lor ( \top \land x)))\\
    64 \tau \sigma(t) &= \tau(\neg (\bot \land (\top \lor ( \top \land x)))) = \neg (\bot \land (\top \lor (\top \land \top)))\\
    65 \end{align*}
    66 
    67 \subsection*{2. $t = \neg(\top \land (\bot \lor y)), s = \neg(x \land (\bot \lor (x \land \bot)))$}
    68 \[\sigma(t) = \sigma(s) \text{ with } \sigma = \{x \mapsto \top, y \mapsto \top \land \bot \} \]
    69 
    70 \subsection*{3.}
    71 Substitution composition is \emph{not} commutative, we give a counterexample.
    72 Let $t = x$, $\sigma = \{x \mapsto \bot\}$ and $\tau = \{x \mapsto \top\}$, it follows:
    73 \[\tau\sigma(t) = \bot\]
    74 \[\sigma\tau(t) = \top\]
    75 We see that $\tau\sigma(t) \neq \sigma\tau(t)$.
    76 
    77 \end{document}